Histopathological changes induced in the gill of an. estuarine mullet, Liza parsia, by sublethal exposure to mercuric chloride - Pandey, A K; George, K C; Mohamed, M Peer (Indian Journal of Fisheries, 2011)
Sublethal exposure of Liza parsia to HgCl2 (0.5 ppm) elicited erratic swimmingpattern, loss of equilibrium and respiratory distress during the initial 24 hrs.On day 2, copious secretion of mucus, swelling (hypertrophy) and vacuolizationof the epithelial lining cells of secondary gill lamellae were noticed. Oedemaand oedematous separation of epidermis from the basement membrane as wellas necrosis and desquamation of epithelial cells were observed by day 4.Oedematous changes, particularly at the base of primary lamellae, tissuehyperplasia and fusion of secondary gill lamellae were seen on day 8 of thetreatment. Extensive cellular hyperplasia, desquamation of epithelial cells,congestion of blood vessels and lamellar telangectases (aneurysms) werefrequently encountered on day 10 and the entire interlamellar spaces becamefilled with the hyperplastic epithelium by day 15 of HgCl2 intoxication